2021
DOI: 10.3390/ijms22116043
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chemically Modified Curcumin (CMC) Analogs Exhibit Anti-Melanogenic Activity in Primary Human Melanocytes

Abstract: Hyperpigmentation is a dermatological condition characterized by the overaccumulation and/or oversecretion of melanin pigment. The efficacy of curcumin as an anti-melanogenic therapeutic has been recognized, but the poor stability and solubility that have limited its use have inspired the synthesis of novel curcumin analogs. We have previously reported on comparisons of the anti-melanogenic activity of four novel chemically modified curcumin (CMC) analogs, CMC2.14, CMC2.5, CMC2.23 and CMC2.24, with that of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
(67 reference statements)
2
14
0
Order By: Relevance
“…1 In the process of melanosome transfer, keratinocyte phagocytosis has recently been 1190 considered as a crucial section. 24 Notably, a recent study suggested that melanocores (the melanin core devoid of surrounding membrane) were internalized by phagocytosis, whereas melanosomes (melanin core with intact surrounding membrane) were internalized by macropinocytosis in keratinocytes. 25 In this study, we confirmed that UVR enhanced the phagocytic ability of keratinocytes, which was regulated by TRPA1.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the process of melanosome transfer, keratinocyte phagocytosis has recently been 1190 considered as a crucial section. 24 Notably, a recent study suggested that melanocores (the melanin core devoid of surrounding membrane) were internalized by phagocytosis, whereas melanosomes (melanin core with intact surrounding membrane) were internalized by macropinocytosis in keratinocytes. 25 In this study, we confirmed that UVR enhanced the phagocytic ability of keratinocytes, which was regulated by TRPA1.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic use of curcumin and chemically modified curcumin (CMC) for inhibiting tyrosinase activity and melanin formation has been reported recently ( Goenka and Simon, 2021 ). However, the poor bioavailability of curcumin and chemically modified curcumin (CMC) limits its application ( Karthikeyan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of melanosome transfer from melanocytes to neighboring keratinocytes is an important mechanism for skin whitening. Recently, Goenka et al reported that chemically modified curcumin analogs suppressed dendricity in melanocytes and inhibited the phagocytosis of FluoSphere beads (melanosome mimics) by HaCaT cells ( Goenka and Simon, 2021 ). The present study expanded upon previous studies and demonstrated that J147 inhibited melanosome transfer to neighboring keratinocytes in the keratinocyte/melanocyte co-culture system ( Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%
“…HEMn-LP cells (1.5 × 10 5 cells/well) or HEMn-DP cells (1.2 × 10 5 cells/well) were cultured in 6-well plates for 24 h followed by the addition of test compounds and further cultured for 6 d. The relative levels of cellular melanin were determined in a manner similar to the method reported in previous studies [ 30 , 31 ]. Briefly, the cells were harvested, washed in PBS, and 150 μL of 1 N NaOH was added and heated to 70 °C to solubilize melanin.…”
Section: Methodsmentioning
confidence: 99%
“…After the treatments, random microscopic fields in each well were imaged at 20× objective magnification. The images were analyzed using an NIS Elements computer-aided image analyzer and two parameters, (i) number of dendrites and (ii) total dendrite length, were quantified in a manner similar to the method reported in previous studies [ 30 , 33 ]. HEMn-DP (3.8 × 10 4 cells/well) was seeded in a 6-well plate for 48 h and compounds was then added for 6 d, and similar measurements were performed.…”
Section: Methodsmentioning
confidence: 99%